Intensitas Anak Menggunakan Smartphone di Masa Pandemi Terhadap Perilaku Anak Sekolah Dasar - Deni Ardiani; Dwi Prasetiyawati DH; Singgih Adhi Prasetyo (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2022)
The purpose of the study was to find out how the behavior development of elementary school children in Puguh Village, Boja District, used smartphones with high intensity during the pandemic. This type of research is qualitative research. The method used is the interview method, and the questionnaire method (questionnaire). The data analysis technique used is to analyze research data, with qualitative analysis to determine the development of children's behavior using smartphones with high intensity during the pandemic. The results showed that the behavioral development of elementary school children in Puguh Village, Boja District who used smartphones with high intensity during the pandemic period was not good, as well as the moral development of children because children had poor manners when talking to older people. In the development of religion, children often delay worship activities. Social development, children spend a lot of time at home playing with smartphones so that their interaction with the community is reduced. Emotional development, children become irritable and emotional. Based on the results of the research and discussion, it was concluded that the use of smartphones with high intensity during the pandemic had a negative impact on the behavioral development of elementary school children.